The Implementation of Bureaucratic Reform Policy from the Perspective of Public Administrative Law and its Impact on Employee Performance at the Garut Regency Personnel and Education and Training Agency - Silvy Vebritha; Widaningsih; Ricky Muhamad Zakaria (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
The performance of civil servants is a key indicator of effective, accountable, and service-oriented local governance. Bureaucratic reform has become a national legal and policy agenda through the Grand Design of Bureaucratic Reform 2010-2025, the Bureaucratic Reform Roadmap 2023-2025, and several administrative law instruments governing institutional strengthening, business process improvement, merit systems, digitalization, and performance accountability. In Garut Regency, the Personnel and Training Agency plays a strategic role in managing civil servant human resources; however, employee performance remains challenged by a gap between relatively high bureaucratic reform achievements and the incomplete internalization of the BerAKHLAK civil servant work culture. This article analyzes the implementation of bureaucratic reform policy from the perspective of public administrative law and its implications for employee performance at the Personnel and Training Agency of Garut Regency. The article is based on a quantitative survey involving 77 respondents. Data were collected using questionnaires and analyzed with multiple linear regression after validity, reliability, and classical assumption tests. The results show that bureaucratic reform has a positive and significant effect on employee performance, with a regression coefficient of 0.514 and a significance value of 0.000. BerAKHLAK work culture also has a positive and significant effect, with a regression coefficient of 0.330 and a significance value of 0.000. Simultaneously, bureaucratic reform and BerAKHLAK work culture explain 63.8% of the variation in employee performance. These findings indicate that bureaucratic reform policy implementation should not be viewed merely as administrative compliance with regulations, but as a public administrative law process requiring consistent implementation, work culture strengthening, leadership, and continuous evaluation